Sugarcane molasses and yeast powder used in the Fructooligosaccharides production by Aspergillus japonicus-FCL 119T and Aspergillus niger ATCC 20611 - Dorta, Claudia; Cruz, Rubens; de Oliva-Neto, Pedro; Camargo Moura, Danilo Jose (Springer, 2006)
Different concentrations of sucrose (3-25% w/v) and peptone (2-5% w/v) were studied in the formulation of media during the cultivation of Aspergillus japonicus-FCL 119T and Aspergillus niger ATCC 20611. Moreover, cane molasses (3.5-17.5% w/v total sugar) and yeast powder (1.5-5% w/v) were used as alternative nutrients for both strains' cultivation. These media were formulated for analysis of cellular growth, P-Fructosyltransferase and Fructooligosaccharides (FOS) production. Transfructosylating activity (U-t) and FOS production were analyzed by HPLC. The highest enzyme production by both the strains was 3% (w/v) sucrose and 3% (w/v) peptone, or 3.5% (w/v) total sugars present in cane molasses and 1.5% (w/v) yeast powder. Cane molasses and yeast powder were as good as sucrose and peptone in the enzyme and FOS (around 60% w/w) production by studied strains.
Keywords: Fructooligosaccharides; Aspergillus japonicus; Aspergillus niger; cane molasses; yeast powder